Parametrização de ligantes em Co(salen) aplicados na despolimerização de ligninas - Costa, Mateus Oliveira (2022)
Since the industrial revolution, fossil sources such as oil, natural gas or coal have become indispensable resources for human development with a variety of uses: from energy generation to drugs production and household items. Nowadays, we possess large reserves of these sources but they are not renewable and studies indicate few decades to run out of them. The use of renewable and non-toxic sources, as biomass, provides an interesting alternative for this dependence on oil and similar. Obtaining fine chemical products from lignin is an interesting alternative for the valorization of biomass, but to achieve it in an efficient, cheap and chemically sustainable way is a challenge. In the present work, we investigate oxidation reactions of lignin models catalyzed by Co(salen) complexes trying to understand which parameters influence the reaction efficiency. Therefore, we used data from the literature to create a statistical model that guided us to the synthesis of catalysts further used in this kind of chemistry, which were evaluated by means of conversion and yield. The reactions performed with the lignin models were parameterized, giving us information about the influences on steric and electronic properties the catalyst ligands must have to maximize the catalytic efficiency.